ZEZWOLENIA W ŚWIETLE PRAWA DZIAŁALNOŚCI GOSPODARCZEJ Polski - Majewska-Otawska, Karolina (Wydział Prawa i Administracji UAM, 2002)
The article deals with the issue of permits for business activity. This institution was regulated in the Business Activity Law Act, which sets out a new legal framework for the public economic law. The long-awaited general regulation of permits, indispensable on a free market, appeared as late as 1999. This paper tries to explain the reasons why lack of previous regulations on permits was a major legal loop in business activity. The Business Activity Law Act defines the legal character of the permits, course of issuing and cancelling them, and the competences of the issuing authorities. The author further discusses the differences between a permit and a licence. The general image of institution regulation has been supplemented with the author>s own remarks and comments in addition to a presentation of the point o f view of the doctrine. A large part of the article is devoted to an analysis of the Business Activity Law Act provisions that determine the permit regulating principles. In the author’s view this issue is especially significant because of its crucial role in creating an ordered and coherent legal system. The underlying assumption o f the Business Activity Law Act is that the rules enforced in this act lay a foundation under a new law that determines business activity principles in general, also being fundamental for separate acts that regulate in detail permit-related procedures. A year after the Act was passed, it is legitimate to carry out an analysis of whether the newly introduced provisions regulating business activity fulfil their function and what their initial effects are on the way towards a comprehensive and ordered legal system. The study conclusions present that there is still a shortage of regulations and the legislators work is delayed. Despite some improvement one can still notice some incoherence in the permit regulations in separate acts as well as contradiction between the Business Activity Law Act and special provisions. As an example and in support of the hypotheses made, several legal acts have been presented with special regulations concerning permits necessary to perform specified types of legal activity.
BUSINESS ACTIVITY PERMITS